Earthquake impacts on microcrustacean communities inhabiting groundwater-fed springs alter species-abundance distribution patterns - Fattorini, Simone (Sci Rep, 2018)
Earthquakes are important natural events, yet their impacts on animal communities are poorly known. Understanding earthquake impacts on groundwater communities is essential to assess their resilience and hence to perform conservation actions. We investigated how a 6.3 M(w) earthquake that occurred in 2009 altered the community structure (diversity, evenness, dominance, species abundance distributions and beta-diversity) of microcrustaceans (Crustacea Copepoda) inhabiting springs fed by the Gran Sasso Aquifer (Central Italy). Sampling was done in low-discharge (1997), high-discharge (2005), and post-seismic (2012) hydrological years. Stygobites (obligate groundwater species) and non-stygobites (non-obligate groundwater species) showed different patterns. A high-water discharge in 2005 altered abundance patterns of non-stygobites. The earthquake re-established former abundance patterns. Stygobites were less affected by high-water discharge in 2005, and showed strong increases in diversity and evenness after the earthquake. This effect was due to the fact that the earthquake induced a strong population decline of previously dominant stygobites (especially of Nitocrella pescei) in the aquifer, and subsequently at the main spring outlets, thus allowing a more equitable species-abundance distribution. These results highlight the importance of considering species ecology to understand the effects of a significant earthquake event on animal communities.